Customer satisfaction in the digital era: the effects of augmented reality experience and advertising personalization - Muhammad Azriel Akbar; Siska Ernawati Fatimah (Jurnal Mantik, 2026)
Advances in digital technology have encouraged the beauty industry to develop marketing strategies that focus on consumer experiences and needs. The use of interactive technology and the delivery of advertisements tailored to consumer interests can increase the ease of shopping as well as customer satisfaction in purchasing skin care products. This study uses a quantitative approach with a survey method. Data was collected through the distribution of questionnaires to 240 respondents who are active users of local brand skin care products Glad2Glow in the city of Cirebon. The sampling technique was carried out using purposive sampling. Data analysis was conducted using variance-based structural equation modeling methods to test the influence of augmented reality experience and advertising personalization on customer satisfaction. The results of the analysis show that augmented reality experiences have a positive and significant effect on customer satisfaction. In addition, advertising personalization also has a positive and significant influence on customer satisfaction. Together, these two independent variables are able to explain most of the variation in customer satisfaction levels. Engaging digital experiences and the delivery of ads that are relevant to consumer needs play an important role in improving customer satisfaction. Therefore, companies need to develop digital marketing strategies that focus on experience, message relevance, and long-term relationships with consumers. This approach is expected to be able to increase brand competitiveness and support business sustainability in the increasingly competitive national and regional digital market on a sustainable basis